(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2024)
In some Arab and Muslim societies, words, such as liberalism, globalization, democracy, and many other foreign terms, have come to people’s ears every now and then. For this reason, it was useful and important to search for their meaning and legal ruling in light of the principles of Islamic law, and whether they are compatible with the constants of Muslim and Arab society, or contradict them. In this research, I will present the meaning of liberalism and the historical and gradual development that this word has reached, then I will discuss the extent of its clash with the true Islamic religion, and its ramifications with politics and economics, in order to reach the results and recommendations at the end of the research.